Perancangan Sistem Informasi Bimbingan Dan Konseling Berbasis Website - Ranti Eka Putri; Yanti Yusman; Indah Puspita Sari (STMIK Budi Darma, 2022)
Guidance and counseling services in schools are efforts organized to facilitate the development of students both individually and in groups according to the needs, talents, potential, interests, conditions and opportunities that students have. BK teachers or counselors are the main implementers of Guidance and Counseling services in schools. Counselors at guidance and counseling institutions (BK) in schools play a role in the process of forming the personality of students, directing students to be better at honing their abilities in the academic field and providing counseling to find solutions, resolve and resolve problems that occur when students experience problem. This role will be effective if guidance and counseling activities are supported by a computerized system. At present, there is still a negative opinion which states that students who are called to come to the counseling room at school are students who have problems or create problems, so most students do not want to do guidance and counseling. Based on these conditions, the researcher is interested in designing a website-based information system for guidance and counseling that can facilitate digitization of guidance and counseling services and can encourage students to be enthusiastic about carrying out guidance and counseling both in personal, social, academic and career terms with openness, independence, and voluntary. This study uses a prototype which will be discussed in subsequent publications. The reason for this website-based information system for bimaling is so that guidance and counseling activities can be carried out anytime anywhere without having to come and deal directly with the counseling teacher.